Penyuluhan Tentang Manfaat Serbuk Masker Wajah di SMK Yapim Biru-Biru - Nerdy Nerdy; Ferry Handika (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The face is the part of the body that is most often noticed compared to other body parts, especially for women. Skin aging is a natural process that cannot be avoided, where humans will experience a slowdown in the process of skin cell renewal and collagen production, weakening of the internal supporting structures and natural protective layers of the skin. The slowing down of the skin regeneration process is caused by environmental factors and lifestyle. The use of this face mask is able to provide freshness as well as blood circulation and open pores to produce optimally clean facial skin so that it leaves a feeling of fresh, beautiful, and relaxed. cognitive development to care about the health and beauty of facial skin from an early age. Where researchers want to conduct counseling on the prevention of dangerous face masks.